Functional Micro–Nano Structure with Variable Colour: Applications for Anti-Counterfeiting. (8th December 2019) - Liu, Hailu; Xie, Dong; Shen, Huayan; Li, Fayong; Chen, Junjia
Abstract : Colour patterns based on micro-nano structure have attracted enormous research interests due to unique optical switches and smart surface applications in photonic crystal, superhydrophobic surface modification, controlled adhesion, inkjet printing, biological detection, supramolecular self-assembly, anti-counterfeiting, optical device and other fields. In traditional methods, many patterns of micro-nano structure are derived from changes of refractive index or lattice parameters. Generally, the refractive index and lattice parameters of photonic crystals are processed by common solvents, salts or reactive monomers under specific electric, magnetic and stress conditions. This review focuses on the recent developments in the fabrication of micro-nano structures for patterns including styles, materials, methods and characteristics. It summarized the advantages and disadvantages of inkjet printing, angle-independent photonic crystal, self-assembled photonic crystals by magnetic field force, gravity, electric field, inverse opal photonic crystal, electron beam etching, ion beam etching, laser holographic lithography, imprinting technology and surface wrinkle technology, etc. This review will provide a summary on designing micro-nano patterns and details on patterns composed of photonic crystals by surface wrinkles technology and plasmonic micro-nano technology. In addition, colour patterns as switches are fabricated with good stability and reproducibility in anti-counterfeiting application. Finally, there will be a conclusion and an outlook on future perspectives.